Peptide Aptamer–Paclitaxel Conjugates for Tumor Targeted Therapy - Xinyang Shen; Yuan Ma; Hang Luo; Razack Abdullah; Yufei Pan; Yihao Zhang; Chuanxin Zhong; Baoting Zhang; Ge Zhang (Pharmaceutics)
Background/Objectives: Traditional paclitaxel therapy often results in significant side effects due to its non-specific targeting of cancer cells. Peptide aptamer–paclitaxel conjugates present a promising alternative by covalently attaching paclitaxel to a versatile peptide aptamer via a linker. Compared to antibody–paclitaxel conjugates, peptide aptamer–paclitaxel conjugates offer several advantages, including a smaller size, lower immunogenicity, improved tissue penetration, and easier engineering. Methods: This review provides an in-depth analysis of the multifunctional peptide aptamers in these conjugates, emphasizing their structural features, therapeutic efficacy, and challenges in clinical applications. Results: This analysis highlights the potential of peptide aptamer–paclitaxel conjugates as a novel and effective approach for targeted cancer therapy. By harnessing the unique properties of peptide aptamers, these conjugates demonstrate significant promise in improving drug delivery efficiency while reducing the adverse effects associated with traditional paclitaxel therapy. Conclusions: The incorporation of peptide aptamers into paclitaxel conjugates offers a promising pathway for developing more efficient and targeted cancer therapies. However, further research and clinical studies are essential to fully unlock the therapeutic potential of these innovative conjugates and enhance patient outcomes.